Tackling Early School Leaving (ESL): main findings from Below 10 project - Mateus, S. (Meeting “DIGITAL TOOL FOR MENTORSHIP AGAINST DROPOUT”, 2022)
This presentation discusses the results of a qualitative research on causes and processes of early school leaving, conducted in 2017 in 8 European cities (Amadora/Portugal, Northampton/United Kingdom, Paris/France, Genova and Cuneo/Italy, Osijek and Djal/Croatia, Bucharest/Romania). The research objectives were: a) to give voice to young people's experiences and the process, causes and effects of early school leaving, retention and dropping out; b) to gather a number of "typical histories" of early school leaving or risks of dropping out that reflect the different situations in which ESL occurs; c) to identify the complex factors, actions, and views underlying ESL not only at individual level but also at school and community levels. The following research questions were address empirically: at local level, what are the factors causing school failure, early school leaving and dropping out? How can ESL and dropping out be reduced? Involving young people and conducting a more critical research process led to young people taking on the role of experts as participants. Around 290 young people who have dropped out of school early, or at risk of dropping out, were involved in focus groups and interviews.